Comparison of Different Body Mass Index Classification Tools to Identify Underweight and Overweight among Young Girls in Rural Haryana - K Srinath; Ravneet Kaur; Mani Kalaivani; Shashi Kant; Puneet Misra; Sanjeev Kumar Gupta (Indian Journal of Public Health)
Malnutrition is prevalent and impactful among young Indian girls aged under 18 years. Systematic errors have been observed in body mass index (BMI) classification among these girls. We assessed anthropometry of 185 young girls (15–17 years) from rural Haryana, and classified BMI using different tools by the World Health Organization (WHO), Center for Disease Control and Prevention (CDC), Indian Academy of Pediatrics (IAP), and extended International Obesity Task Force (IOTF). Agreement between various tools with extended IOTF cutoffs was expressed by Cohen’s weighted kappa. The WHO and IAP charts demonstrated moderate agreement with extended IOTF cutoffs. The CDC chart did not distinguish severe underweight and underweight. Extended IOTF Asian cutoffs are context-specific, able to classify all five weight categories, have smooth transition to adult BMI standards, and suitable for identifying underweight and overweight. This study emphasizes need for developing and using accurate BMI classification tools, to improve the efficiency of addressing malnutrition among young rural Indian girls.